Long‐billed curlew nest site selection and success in the intermountain west. Issue 5 (22nd May 2019) - Coates, Stephanie E.; Wright, Benjamin W.; Carlisle, Jay D.
ABSTRACT: Grassland birds have experienced steeper population declines between 1966 and 2015 than any other bird group on the North American continent, and migratory grassland birds may face threats in all stages of their annual cycle. The grassland‐associated long‐billed curlew ( Numenius americanus ) is experiencing population declines in regional and local portions of their North American breeding range. The nesting period is an important portion of the annual cycle when curlews may face demographic rate limitations from a suite of threats including predators and anthropogenic disturbance. We compared nest sites to random sites within breeding territories to examine nest site selection, and modeled correlates of nesting success for 128 curlew nests at 5 Intermountain West sites. Nest sites were 6 times more likely than random sites to be situated adjacent to existing cowpies. Additionally, curlews selected nest sites with shorter vegetation, and less bare ground, grass, and shrub cover than at random sites within their territories. Nest success varied widely among sites and ranged from 12% to 40% in a season with a mean of 27% for all nests during the 2015 and 2016 seasons. Higher nest success probability was associated with higher curlew densities in the area, greater percent cover of conspicuous objects (cowpies, rocks) near the nest, and higher densities of black‐billed magpies ( Pica hudsonia ) and American crows ( Corvus brachyrhynchos ) at the site. We also found increased probability of nesting success with increased distance from a nest to the nearest potential perch in that territory. Given the central role of working lands to curlews in much of the Intermountain West, understanding limitations to nesting success in these diverse landscapes is necessary to guide adaptive management strategies in increasingly human‐modified habitats. We suggest some grazing and irrigation practices already provide suitable nesting conditions for curlews, and others may require only minor temporal shifts to improve compatibility. © 2019 The Wildlife Society. Abstract : Long‐billed curlew nest success was positively correlated with the presence of conspicuous objects (e.g., cowpies, rocks), increasing distance between the nest and the nearest potential perch, higher densities of magpies and crows, and higher density of curlews near the nest territory. Curlews selected nest sites with increased visibility of their surroundings and that were near existing cowpies. Our results suggest that nesting curlews may benefit from some aspects of cattle grazing, and nesting success might be improved through reduction of potential perches for avian predators and preserving breeding areas with high curlew density.